Aortoduodenal fistula after abdominal aortic aneurysm resection: Two case reports - Tomić, Aleksandar; Marjanović, Ivan; Kostić, Zoran; Mitrović, Miroslav; Slavković, Damjan; Vasković, Igor; Jevtić, Aleksandar; Sekulić, Dragan (Vojnosanitetski pregled, 2021)
Introduction. Aortoenteric fistula (AEF) is rare and extremely difficult complication of aortic surgery. We presented two cases of secondary aortoduodenal fistula (SADF) as complication after aortic surgery. Case reports. In the first patient SADF happened 11 years after open abdominal aneurysmal resection with gastrointestinal tract (GIT) bleeding. After negative esophagogastroduodenoscopy (EGDS) we performed multislice computed tomography (MSCT) which revealed contrast leakage in duodenum from 10 cm wide visceral aortic aneurysm. The patient was treated with graft excision, aneurysmal reduction, sewing of proximal and distal aortal stumps, bowel repair followed by axillobifemoral bypass (AxFF). The patient dismissed on 30th postoperative day. The second case of ADF happened five months after endovascular reconstruction of abdominal aorta with GIT bleeding and fewer. During following 8 days, he had three negative EGDS. On MSCT we found signs of endoleak, free air in aneurysmal sac, and signs of blood in the intestine. On urgent operation we extracted stent graft, sewed proximal and distal aortal stumps, performed bowel repair and AxFF. The patient died a day after operation with signs of sepsis and multiple organ failure syndrome. Conclusion. Conventional treatment of ADF means extraanatomic AxFF with complete excision of infected graft or stent graft, with closure of aorta’s proximal and distal stumps and duodenal repair. Because of high mortality, prompt diagnostic evaluation and quick decision of an adequate operative treatment is necessary. Although European Society of Vascular Surgery recommendations, as a guide, are very helpful, there is no unique attitude about management of AEF, so each patient should be specifically treated.